Assessment of Conventional and Low Gossypol Cottonseed Meal as Alternative Protein Sources in Low-Fishmeal Diets of Hybrid Grouper (Epinephelus fuscoguttatus♀× Epinephelus lanceolatus♂): Growth, Feed Utilization, Gut Histology, and Immunity - Misbah Irm; Bo Ye; Xiaoyi Wu; Lina Geng; Qinxiao Cai; Lu Zhang; Haoyun Zhai; Zhiyu Zhou (Animals, 2022)
A 9-week growth trial was carried out to assess the influence of replacing poultry by-product meal protein with conventional cottonseed meal protein (CCMP) or low gossypol cottonseed meal protein (LGCMP) on growth, feed utilization, gut micromorphology, and immunity of hybrid grouper (Epinephelus fuscoguttatus♀× Epinephelus lanceolatus♂) juveniles fed low-fish meal (18.53%, dry matter) diets. Eleven experimental diets were prepared. The control diet (PBMP) contained 46.15% poultry by-product meal protein. Both conventional cottonseed meal protein (CCMP) and low-gossypol cottonseed meal protein (LGCMP) were used in replacement ratios of 20, 40, 60, 80, and 100% of poultry by-product meal protein (PBMP) from the control diet, forming ten experimental diets (CCMP20, CCMP40, CCMP60, CCMP80, CCMP100, LGCMP20, LGCMP40, LGCMP60, LGCMP80, and LGCMP100). Results demonstrated that weight-gain percentage (WG%) was not different between different sources of cottonseed meal (CCMP and LGCMP). However, values of WG% significantly differed among different replacement levels, with CCMP80 and LGCMP40 having significantly higher values compared to other treatments. Fish fed CCMP80 and LGCMP40 exhibited higher protein efficiency ratios (PERs) than fish fed other experimental diets. The regression analysis from a second-order or third-order polynomial model based on WG% showed that the optimal PBMP replacement levels by CCMP and LGCMP are 74% and 33%, respectively. The whole-body lipid contents remarkably decreased as dietary CCMP or LGCMP inclusion levels increased. The relative mRNA expression of insulin-like growth factor-1(IGF-1) in liver was higher in fish fed CCMP80 and LGCMP40 diets compared to fish fed other diets. Generally, in low-FM diets of hybrid grouper, CCMP and LGCMP could replace 74% and 33% of PBMP, respectively.